MANAGEMENT SUMMARY EXECUTIVE PENJUALAN BERBASIS APLIKASI DIGITAL DIMASA PANDEMI - Kotim Subandi; Dinar Munggaran Akhmad; Adriana Sari Aryani (Universitas Pancasila, 2022)
The development of social media and marketplaces as part of information technology has a very big contribution in developing business. Current developments have also changed the pattern and map of competitive forces in running a business to become more competitive. Therefore, reliability in the use of social media and marketplaces is an important and strategic thing that is needed by business people. But this is in stark contrast to business people who are still in the pioneering stage or just starting their business, such as Lagsana Ummy Hunny. Capitalized on knowledge and insight that is still new to social media and marketplaces, it is quite influential in developing managed businesses. Therefore, this community service activity aims to increase the insight and knowledge of the Lagsana MSME owner, Ummy Hunny, located in the Bojong Gede area, Bogor Regency, in the use of social media and marketplaces for the benefit of developing business. The method that will be used to support the implementation of community service activities such as providing training and assistance to increase knowledge and insight. Knowledge and insight applied to this activity is how to utilize an information technology. Information technology is used to develop the marketing reach of the general public through social media. This activity has been going well and has contributed to increasing sales through the Dogital Application. The use of Digital Applications is very helpful in increasing sales because of the information from the menu variants sold through social media.